High resolution analysis of the н12 band and re-analysis of the ground vibrational state of cis-d2-ethylene; The XVIIIth Symposium and School on High Resolution Molecular Spectroscopy, June 30 - July 4, 2015, Tomsk, Russia - Chertavskikh Yu. V. Yulia Vladimirovna (2015, 2015)
Title screen